Strategic leadership and management in nonprofit organizations : theory and practice - Golensky, Martha; Hager, Mark A. (New York: Oxford University press, 2020)
""Nonprofit organizations need smart, informed managers. This introductory textbook aims to expose students to the range of responsibilities expected from modern nonprofit organizations, their boards, their executive management, their frontline staff, and their community volunteers. Featuring an extended case study, the book is aimed at students and professionals. Section 1 focuses on the characteristics of a nonprofit organization, with an explanation of the specific attributes of both charitable and member-serving nonprofits. It consider the historical development of the nonprofit sector as a whole and of the human services subsector in particular. The section culminates with a review of the political and economic climate in which nonprofits operate. Section 2 considers general theories of leadership. The multiple roles of the nonprofit professional leader are delineated, to recognize that the same person may serve as manager and administrator, motivated by different priorities when functioning in each capacity. Ethical issues are also considered, along with the theoretical and practical aspects of decision-making, and the relationship between organizational culture and organizational change. Sections 3 and 4 address the specific skills of the nonprofit leader involved in securing material resources and managing human resources, respectively. In section 3, strategic planning, program planning and evaluation, resource generation, organizational performance indicators, and technology and communication are the areas of emphasis. Section 4 includes chapters dealing with leadership to create and protect a culture of integrity, human resource management, and the practical aspects of board governance. The book concludes with a focus on the role of volunteers and the need for organizations to provide them good experiences if they want volunteers to keep coming back.""--
Revised edition of Strategic leadership and management in nonprofit organizations, c2011.
Keywords: Nonprofit organizations -- Management; Nonprofit organizations; Strategic planning